631.859.13 Kimyo va kimyoviy texnologiyalar: Rheological properties of ammophosphate pulps obtained using phosphorite powder of the Khodjakul deposit - Yusupov, Muzafar; Kurbaniyazov, Rashid; Reymov, Axmed; Pirnazarov, Bakhtiyar; Namazov, Shafoat; Badalova, Oydin; Beglov, Boris (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The rheological characteristics (density, viscosity) of acidic and ammoniated phosphate slurries obtained from the decomposition of Khodjakul phosphate powder with extraction phosphoric acid (EPA) in a wide range of acid : phosphorite mass ratio and temperatures were studied. It has been shown that both acidic and ammoniated pulps have high fluidity and can be transported by pumping devices without any restrictions. Methods. Experiments on the decomposition of phosphorite powder (PP) with phosphoric acid were carried out in a tubular glass reactor equipped with a screw stirrer driven by a motor. The required amount of EPA was placed in the reactor and heated to 65°C. Phosphate raw materials were introduced into the reactor with an EPA attachment. The mass ratio of EFA :PP was chosen in the range of 100: (5-30). The density of acid phosphate pulps was determined by the pycnometric method with a measurement accuracy of 0.05 rel. %, and kinematic viscosity - using a glass capillary viscometer VPJ-1 with an error of 0.2 relative to % in the temperature range of 20-90 0C. Results. Laboratory experiments have established that the most optimal mass ratios of EFA :PP is 100:20 and 100:25. Under these conditions, the ammonium phosphate pulp at a temperature of 60°C has a density and viscosity of 1.32-1.34 g/cm3 and 20.06-24.13 centipoise, respectively. Conclusion. In the range of 20-90oC, the density and viscosity of acid phosphate pulps obtained from the decomposition of phosphorite powder Khojakul with phosphoric acid in a wide range of initial components (EFA :PP = 100:5-30). It is shown that the pulps have high fluidity (no more than 1.37 g/cm3 and 7.08 centipoise).